Recycling Strategies for Ceramic All-Solid-State Batteries—Part I: Study on Possible Treatments in Contrast to Li-Ion Battery Recycling - Lilian Schwich; Michael Küpers; Martin Finsterbusch; Andrea Schreiber; Dina Fattakhova-Rohlfing; Olivier Guillon; Bernd Friedrich (Metals, 2020)
In the coming years, the demand for safe electrical energy storage devices with high energy density will increase drastically due to the electrification of the transportation sector and the need for stationary storage for renewable energies. Advanced battery concepts like all-solid-state batteries (ASBs) are considered one of the most promising candidates for future energy storage technologies. They offer several advantages over conventional Lithium-Ion Batteries (LIBs), especially with regard to stability, safety, and energy density. Hardly any recycling studies have been conducted, yet, but such examinations will play an important role when considering raw materials supply, sustainability of battery systems, CO2 footprint, and general strive towards a circular economy. Although different methods for recycling LIBs are already available, the transferability to ASBs is not straightforward due to differences in used materials and fabrication technologies, even if the chemistry does not change (e.g., Li-intercalation cathodes). Challenges in terms of the ceramic nature of the cell components and thus the necessity for specific recycling strategies are investigated here for the first time. As a major result, a recycling route based on inert shredding, a subsequent thermal treatment, and a sorting step is suggested, and transferring the extracted black mass to a dedicated hydrometallurgical recycling process is proposed. The hydrometallurgical approach is split into two scenarios differing in terms of solubility of the ASB-battery components. Hence, developing a full recycling concept is reached by this study, which will be experimentally examined in future research.